Presidential Decree No. 115/2015 Promulgating the Law Regulating Movable Guarantees = قرار رئيس جمهورية مصر العربية رقم 115 لسنة 2015 بإصدار قانون تنظيم الضمانات المنقولة / presidency - Egypt. presidency (2025)
Presidential decree-law no. 115 of the year 2015 promulgating the law regulating movable guarantees – chapter 1: definition and scope application – chapter 2: registry of movable guarantees – chapter 3: rules of registration of security interest against in the registry – chapter 4: perfection of the security interest against third parties – chapter 5: effects of registration of the security interest – chapter 6: execution against movable assets and ranking of creditors’ rights – chapter 7: penalties قرار رئيس جمهورية مصر العربية بالقانون رقم 115 لسنة 2015 باصدار قانون تنظيم الضمانات المنقولة – الفصل الاول التعريفات ونطاق التطبيق – الفصل الثانى سجل الضمانات المنقولة – الفصل الثالث قواعد شهر حق الضمان بالسجل – الفصل الرابع نفاذ حق الضمان تجاه الغير – الفصل الخامس الآثار المترتبة على شهر حق الضمان – الفصل السادس التنفيذ على المنقول وترتيب حقوق الدائنين – الفصل السابع العقوبات